Mediated education in early modern travel stories: How travel stories contribute to children's empirical learning. Issue 2 (June 2019) - Dietz, Feike
Argument: Linking up with recent studies on the experience of space and place in modern youth literature, this article analyzes how the "journey" as a narrative line and motif transformed Dutch early modern travel books for children from classical teaching instruments into explorative knowledge places. In the popular seventeenth-century Glorious and Fortunate Journey to the Holy Land, young readers were invited to travel within the book, which was presented as a place that covers material pages to observe as well as imagined places to read about. Eighteenth-century travel books, for example written by Joachim Heinrich Campe, shifted from an inner to an empirical mode of travelling. They raised the suggestion that they offered unmediated observations and travel experiences, as if reading about places was equal to seeing places. Since travel literature facilitated active knowledge quisition among youngsters, but also left little room for autonomous innovations or different interpretations, this article reveals the emancipatory as well as restrictive character of such places of learning. By turning reading into a kind of travelling, travel books served as a substitute for travel.